2009
DOI: 10.12973/ejmste/75259
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effect of Mathematics Teaching Provided Through Drama on the Mathematics Ability of Six-Year-Old Children

Abstract: This study was conducted to examine the effect of mathematics teaching given through the drama method on the mathematical ability of six-year-old children. The research was conducted in Ankara on 105 children from the kindergarten classes of two different primary schools of the Ministry of National Education, which are at middle socioeconomic level. Thirty-five of the 105 children were selected as the experimental group, 35 of them as the control group and finally 35 as the placebo control group. The placebo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
(10 reference statements)
1
10
0
6
Order By: Relevance
“…Math and Science Across Cultures (Bazin et al 2002), as well as Math Around the World (Lawrence Hall of Science/UCB 1995) are striking examples of the application of real-world situations to mathematics education for students starting at age 9 all the way up to College. "A Study on the Effect of Mathematics Teaching Provided Through Drama" (Erdogan and Baran 2009), "A Study on the role of Drama in Learning Mathematics" (Masoum et al 2013), and Math for Humans: Teaching Math Through 8 Intelligences (Wahl 1999) are valuable contributions. The value of story-telling has been emphasized throughout the chapters in this book but the use of drama in communicating mathematical concepts and ideas also deserves attention.…”
Section: Successes Of Indigenous Mathematics Educationmentioning
confidence: 99%
“…Math and Science Across Cultures (Bazin et al 2002), as well as Math Around the World (Lawrence Hall of Science/UCB 1995) are striking examples of the application of real-world situations to mathematics education for students starting at age 9 all the way up to College. "A Study on the Effect of Mathematics Teaching Provided Through Drama" (Erdogan and Baran 2009), "A Study on the role of Drama in Learning Mathematics" (Masoum et al 2013), and Math for Humans: Teaching Math Through 8 Intelligences (Wahl 1999) are valuable contributions. The value of story-telling has been emphasized throughout the chapters in this book but the use of drama in communicating mathematical concepts and ideas also deserves attention.…”
Section: Successes Of Indigenous Mathematics Educationmentioning
confidence: 99%
“…Similarly, Catterall and Waldorf (1999) reported that children in Chicago arts-integrated elementary schools perform better on tests than those in control schools. In the field of early childhood education, Erdoğan and Baran (2009) reported that drama-infused mathematics instruction for Turkish six year-olds was associated with their mathematics achievement test scores. Researchers have also found nonacademic effects in studies of arts integration; for example, teachers and classroom observers have reported improvements in students' creative and critical thinking abilities after arts-integrated programming (Curva and Associates, 2005;Randi Korn & Associates, 2005;Randi Korn & Associates, 2010).…”
Section: Arts Integrationmentioning
confidence: 99%
“…Categories of such drama include: (i) context building action -'setting the scene' or adding information to a dramatic context; (ii) narrative action -telling a "story" or "what-happens-next"; (iii) poetic action -creating 4 symbolism; and (iv) reflective action -using "soliloquy" or "inner thinking" within dramatic context (Neelands & Goode, 2005). Educational drama has been widely used successfully in schools, within diverse subject disciplines, including sex education (Lloyd & Lyth, 2003), English as a second language (Demircioğlu, 2010), mathematics (Erdoğan & Baran, 2009) and the nature of science (Boujaoude, Sowwan & Adb-El_Khalick, 2005). However, while educational drama by the teacher or trained actors can generate high levels of interaction and engagement with students (e.g., Boggs, Mickel & Holtom, 2007), some students may be hesitant to actually participate in active role play themselves, due either to personal shyness and/or cultural influences (authors' obs.…”
Section: Use Of Drama and Puppetry In Educationmentioning
confidence: 99%